2019
DOI: 10.3390/nu11123047
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-Reported Exposure to Sugar-Sweetened Beverage Promotions and Intake: Cross-Sectional Analysis of the 2017 International Food Policy Study

Abstract: Sugar-sweetened beverage (SSB) consumption is independently associated with several non-communicable diseases, so policymakers are increasingly implementing measures, such as marketing regulation, to reduce intake. To help understand how such measures work, this study examined the association between SSB consumption and self-reported exposure to SSB promotions, both overall and by type of promotion, and whether these relationships vary between the UK, USA, Canada, Mexico, and Australia. Cross-sectional analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
(45 reference statements)
1
21
0
1
Order By: Relevance
“…Education was categorized as "low," "medium," or "high" according to country-specific criteria of the highest level of formal education attained. These categorizations of race/ethnicity and education are consistent with prior IFPS research (Forde et al, 2019;Kwon et al, 2019;Vanderlee et al, 2021).…”
Section: Sociodemographic Variablessupporting
confidence: 84%
“…Education was categorized as "low," "medium," or "high" according to country-specific criteria of the highest level of formal education attained. These categorizations of race/ethnicity and education are consistent with prior IFPS research (Forde et al, 2019;Kwon et al, 2019;Vanderlee et al, 2021).…”
Section: Sociodemographic Variablessupporting
confidence: 84%
“…Open access mixed, but some studies have found that exposure to less healthy food and drink advertising influences purchasing and consumption, and normalises the consumption of less healthy foods and drinks. [9][10][11][12][13][14] Advertising exposure may therefore be a plausible influence on obesity and diet-related non-communicable diseases. 15 16 A systematic review found that children from ethnic minority and socioeconomically disadvantaged backgrounds were disproportionately exposed to advertising for less healthy foods.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Within each question, 19 places where advertisements may have been seen or heard were specified. Using methods adapted from Forde et al, 12 we recategorised the 19 places into five advertising settings prior to analysis: traditional advertising, digital advertising, advertising in recreational environments, advertising in functional environments and advertising across transport networks (table 1). Participants were also able to report other places using free text.…”
Section: Measuring Exposure To Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this lack of effect occurs following sustained exposure is unknown as studies testing effects of repeated exposure to palatable food advertisements in adults are lacking. However, it was recently reported in an international population of 15,515 adults that consumption of SSB was positively associated with self-reported exposure to SSB marketing [ 146 ]. Interestingly, the type of SSB marketing that showed the strongest correlation to SSB consumption was via digital media (online/Internet ads; mobile app/video game; social media (e.g., Twitter, Facebook, and Snapchat)).…”
Section: Introductionmentioning
confidence: 99%